A comparison of heart failure patients with reduced ejection fraction in the Moravian Midlands Registry with the LCZ696 patients in the Paradigm-HF trial - Pavlů, Luděk; Vícha, Marek; Flašík, Jakub; Petřková, Jana; Táborský, Miloš; Schovánková, Tereza; Holý, Ondřej (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND AND AIMS: There are limited data on real clinical practice in heart failure patients in the Czech Republic. We analysed the clinical parameters from the Moravian Midlands Registry (MMR) and compared them to LCZ696 patients in the Paradigm-HF trial. The Moravian Midlands Registry is a retrospective patient database from two outpatient cardiology centres in the Czech Republic. The Paradigm-HF is a large-scale prospective randomized multicentre trial with more than 8000 individuals with stabilized chronic heart failure. METHODS: A retrospective analysis of heart failure with reduced ejection fraction patients from two outpatient cardiology centres in the Czech Republic from October 2016 to December 2019. RESULTS: Patients in the MMR were younger (60.5 ± 10.7 vs 63.8 ± 11.5 years, P<0.05), had a higher body mass index (30.3 ± 5.0 vs 28.1 ± 5.5, P<0.05) and higher serum creatinine level (101.9 ± 36.0 vs 99.9 ± 26.5 μmol/L, P<0.05). MMR patients had lower left ventricular ejection fraction (27.8 ± 6.9 vs 29.6 ± 6.1%, P<0.05). The serum N-terminal pro-B-type natriuretic peptide, [2563.5 (377-3536) vs 1631 (885-3154), was non significantly higher P=0.07]. Pharmacotherapy use differed for mineralocorticoid antagonist (91.4% in MMR vs 54.2% in Paradigm-HF), and digoxin (13.5% vs 29.2%). Beta-blocker use was similar (96.2% vs 93.1%) as was angiotensin-converting enzyme (ACE) inhibitors - (71.2% vs 78.0%) and angiotensin-receptor blockers - ARB (27.9% vs 22.2%). Dosages of the commonly used ACE inhibitors at the screening visit (Paradigm-HF) / before angiotensin receptor-neprilysin inhibitor administration (MMR) differed significantly only for ramipril (7.0 ± 3.1 mg vs 4.8 ± 2.9 mg, P<0.05), dosages of ARB were - losartan (67.1 ± 30.2 vs 39.6 ± 32.0 mg, P=0.09) and valsartan (181.5 ± 71.1 vs 130.9 ± 82.2 mg, P=0.07). There was a substantial difference in device-based therapy (ICD in 60.6%, CRT 25.9% in MMR vs 14.9% and 7.0% in Paradigm-HF). CONCLUSION: The differences between the groups for the majority of clinical parameters compared were minimal, except for younger age, higher body mass index and serum creatinine level and lower left ventricular ejection fraction and substantially lower dosage of administered ramipril prior to commencing sacubitril/valsartan therapy. There was a higher prevalence of implantable cardioverter-defibrillators (ICD) and cardiac resynchronization therapy (CRT) in the MMR group.
Keywords: Stroke Volume; aminobutyráty; Female; antagonisté receptorů pro angiotenzin; fixní kombinace léků; ženské pohlaví; Heart Failure; Registries; lidé; srdeční selhání; Tetrazoles; Natriuretic Peptide, Brain; tetrazoly; Valsartan; retrospektivní studie; natriuretický peptid typu B; Male; Aged; Czech Republic; valsartan; bifenylové sloučeniny; tepový objem; Aminobutyrates; Česká republika; lidé středního věku; registrace; senioři; mužské pohlaví; Biphenyl Compounds; Angiotensin Receptor Antagonists; Retrospective Studies; Middle Aged; Drug Combinations; Humans